The Discussion About the Family in Polish Newspapers and Magazines in the Second Half of the 19th and at the Beginning of the 20th Century - Walasek, Stefania (Pedagogika, 2014)
The aim of the article is to present the work for the family carried out at the turn of the 19th and 20th century. The reports, comments, and information included in the article show the beginnings of educational and pre-school institutions. They serve as a proof of the activity aimed at supporting the family undertaken by a part of the society of Poland.